2020
DOI: 10.1371/journal.pone.0230191
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment and source identification of heavy metal pollution in vegetable bases of Urumqi, China, using the positive matrix factorization (PMF) method

Abstract: Heavy metal pollution is a widespread problem and strongly affects human health through the food chain. In this study, the overall pollution situation and source apportionment of heavy metals in soil (Hg, Cd, As, Pb, Ni, Zn, Cu and Cr) were evaluated using various methods including geo-accumulation index (I geo), potential ecological risk index (RI) and positive matrix factorization combined with Geographical Information System (GIS) to quantify and identify the possible sources to these heavy metals in soils.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
(65 reference statements)
0
24
0
Order By: Relevance
“…In various studies, this factor is used to determine the degree of environmental risk. So, Kuerban et al (2020) used this index to determine environmental risk. The results showed that the Xinjiang oasis area had a low environmental risk due to the low values of PERI.…”
Section: Results Of Plimentioning
confidence: 99%
“…In various studies, this factor is used to determine the degree of environmental risk. So, Kuerban et al (2020) used this index to determine environmental risk. The results showed that the Xinjiang oasis area had a low environmental risk due to the low values of PERI.…”
Section: Results Of Plimentioning
confidence: 99%
“…However, the mean concentrations of Cd, Co, Pb and Zn were exceeded their background values, which can demonstrate that the soils of the studied area are polluted with these metals by the anthropogenic activities 23 . In the same line, higher contents of Cd, Pb, Cu, Zn were observed in vegetable elds in China 30 . The main contribution of trace metals to agricultural soils is the use of chemical fertilizers, pesticides and organic fertilizers 5,17,30 .…”
Section: Resultsmentioning
confidence: 60%
“…In the same line, higher contents of Cd, Pb, Cu, Zn were observed in vegetable elds in China 30 . The main contribution of trace metals to agricultural soils is the use of chemical fertilizers, pesticides and organic fertilizers 5,17,30 . Thus, Cd, Co, Pb and Zn require more attention in the future, and continuous monitoring of the application of agrochemicals in the production of vegetables is recommended to decrease the probable ecological risks caused by these trace metals in soils of the Eastern Nile Delta.…”
Section: Resultsmentioning
confidence: 60%
“…Data for 2000–2018 are from Zeng et al ( 14 ). Data for 2019–2020 are compiled from Ali et al ( 35 ), Chai et al ( 36 ), Chen et al ( 37 ), Guan et al ( 38 ), Guo et al ( 39 ), Han et al ( 40 ), Hou et al ( 41 ), Hu et al ( 42 ), Huang et al ( 43 ), Jiang and Guo ( 44 ), Jin et al ( 45 ), Jin et al ( 46 ), Lu et al ( 47 ), Lv and Sun ( 48 ), Song et al ( 49 ), Wang et al ( 50 ), Wu et al ( 51 ), Xiao et al ( 52 ), Yang et al ( 53 ), Zhao et al ( 54 ), Zhou et al ( 55 ), Bao et al ( 56 ), Cao et al ( 57 ), Chai et al ( 58 ), Cheng ( 59 ), Duan et al ( 60 ), Guo et al ( 61 ), He et al ( 62 ), Hu et al ( 63 ), Ji et al ( 64 ), Kuerban et al ( 65 ), Li et al ( 66 ), Ma et al ( 67 ), Miao et al ( 68 ), Peng et al ( 69 ), Shi et al ( 70 ), Su and Yang ( 71 ), Sun et al ( 72 ), Tan et al ( 73 ), Tang et al ( 74 ), Wei et al ( 75 ), Xiao et al ( 76 ), Zhang et al ( 77 ), Zhang et al ( 78 ), Zhao et al ( 79 ), Zhuang et al ( 80 ).…”
Section: The Impact Of Pollution On Food Safety In Chinamentioning
confidence: 99%